2015
DOI: 10.1038/nmat4455
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional superconductivity at mesoscopic point contacts on the 3D Dirac semimetal Cd3As2

Abstract: Since the three dimensional (3D) Dirac semi-metal Cd 3 As 2 exists close to topological phase boundaries, in principle it should be possible to drive it into exotic new phases, like topological superconductors, by breaking certain symmetries. Here we show that the mesoscopic point-contacts between silver (Ag) and Cd 3 As 2 exhibit superconductivity up to a critical temperature (onset) of 6 K while neither Cd 3 As 2 nor Ag are superconductors. A gap amplitude of 6.5 meV is measured spectroscopically in this pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
178
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(192 citation statements)
references
References 36 publications
8
178
0
4
Order By: Relevance
“…Interestingly, we also notice two recent point contact studies on Cd 3 As 2 polycrystal and single crystal, respectively. 43,44 In both studies, indication of superconductivity was found around the point contact region on the surface, with T c comparable to ours. In particular, no superconductivity is observed by the 'soft' point contact technique, therefore it was suggested that the superconductivity observed around the point contact region under the 'hard' tip might be induced by the local pressure.…”
Section: Pressure-induced Superconductivitysupporting
confidence: 87%
“…Interestingly, we also notice two recent point contact studies on Cd 3 As 2 polycrystal and single crystal, respectively. 43,44 In both studies, indication of superconductivity was found around the point contact region on the surface, with T c comparable to ours. In particular, no superconductivity is observed by the 'soft' point contact technique, therefore it was suggested that the superconductivity observed around the point contact region under the 'hard' tip might be induced by the local pressure.…”
Section: Pressure-induced Superconductivitysupporting
confidence: 87%
“…Recently, theoretical investigations have proposed that the Dirac semimetal Cd 3 As 2 is promising for topological superconductivity [17,18]. In addition, the signatures of unconventional superconductivity in Cd 3 As 2 have been reported through pressure-loaded [19] and point-contacted [20,21] experiments. However, the proximity effect-induced superconductivity in Cd 3 As 2 has still not yet been achieved, which is more important for practical devices without complicated pressure loading.…”
Section: Introductionmentioning
confidence: 99%
“…On the experimental side, the availability of the honeycomb optical lattice 18 and the tunable attractive interaction by Feshbash resonance 19 give a possible test ground for this study. Besides, the expected unique feature of the Higgs mode in superconducting Dirac semimetal can be used as an important experimental characterization to distinguish it from the normal superconductors 21,22 . In this paper we study the quenched dynamics in the weak coupling limit by using the Anderson pseudo-spin formalism 23 .…”
Section: Introductionmentioning
confidence: 99%